2007
DOI: 10.1016/j.jsat.2006.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Innovation adoption in substance abuse treatment: Exposure, trialability, and the Clinical Trials Network

Abstract: Researchers and policymakers are increasingly focusing on factors that facilitate or impede the diffusion of evidence-based treatment techniques into routine clinical practice. One potentially fruitful avenue of research is the influence of involvement in research networks as a predictor of organizational innovation. The Clinical Trials Network (CTN) is examining a number of behavioral and pharmacological treatment techniques in controlled multisite studies. Using data from participating CTN treatment programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
151
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 31 publications
5
151
0
Order By: Relevance
“…A comparison of the CTN and a nationally representative sample of drug abuse treatment units controlled for organizational variables and suggested that participation in the buprenorphine clinical trials was associated with increased adoption of buprenorphine (20% versus 11%) (Ducharme, et al, 2007). Participation in the CTN, however, did not enhance adoption of contingency management strategies (34% versus 31%).…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of the CTN and a nationally representative sample of drug abuse treatment units controlled for organizational variables and suggested that participation in the buprenorphine clinical trials was associated with increased adoption of buprenorphine (20% versus 11%) (Ducharme, et al, 2007). Participation in the CTN, however, did not enhance adoption of contingency management strategies (34% versus 31%).…”
Section: Limitationsmentioning
confidence: 99%
“…Participation in the CTN, however, did not enhance adoption of contingency management strategies (34% versus 31%). The study also noted that CTN participants were less likely to operate as for-profit corporations (12% versus 18%), less likely to offer detoxification services (19% versus 29%), more likely to treat opiate dependent patients (42% with a primary opiate problem versus 16%), and more likely to report JCAHO or CARF accreditation (66% versus 48%) (Ducharme, et al, 2007). CTN and non-CTN programs did not differ on percent of revenues from public sources (about 50%), physicians on staff or contract (about 70%), and counselors with Master's degrees (45%).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Considerable work has examined its diffusion in SUD treatment programs and OTPs (Brigham et al, 2007;Ducharme & Abraham, 2008;Ducharme et al, 2007;Friedmann et al, 2010;Gordon et al, 2007;Knudsen et al, 2006Knudsen et al, , 2009Koch et al, 2006;Kovas et al, 2007;Wallack et al, 2010). Several surveys of physicians have examined the nexus between attitudes and prescribing (Arfken et al, 2010;Kissin et al, 2006;Netherland et al, 2009;Reif et al, 2007;Thomas et al, 2008;WESTAT, 2006).…”
mentioning
confidence: 99%
“…Studies on the availability of SUD pharmacotherapies in specialty treatment organizations have often focused on the diffusion of specifi c medications, such as buprenorphine, acamprosate, and naltrexone (Abraham et al, 2010Ducharme et al, 2006Ducharme et al, , 2007Friedmann et al, 2010;Koch et al, 2006;Roman, 2007, 2008;Roman et al, 2011;Savage et al, 2012;Thomas et al, 2003Thomas et al, , 2008. In addition, research has considered the organizational factors associated with the availability of any type of SUD medication Knudsen et al, 2010Knudsen et al, , 2011, in part because the adoption of at least one medication is correlated with offering other pharmacotherapies (Fuller et al, 2005).…”
mentioning
confidence: 99%